Interleukin-26 Expression in Inflammatory Bowel Disease and Its Immunoregulatory Effects on Macrophages - Song, Dongjuan; Lai, Lijie; Lu, Juntao; Tong, Jinlu; Ran, Zhihua (Frontiers in Medicine, 2022)
Background and Aim: Interleukin-26 (IL-26) has been implicated in several chronic inflammatory diseases. However, its role in inflammatory bowel disease (IBD) remains to be elucidated. We aimed to investigate IL-26 expression in IBD and its immunoregulatory effects on macrophages. Methods: We assessed IL-26 expression in the intestinal mucosa and blood samples of IBD patients and healthy controls (HC). The associations between the clinical characteristics of IBD and IL-26 expression levels in serum and peripheral blood mononuclear cells (PBMCs) were investigated. In addition, the transcriptional changes in THP-1 macrophages exposed to IL-26 were determined by RNA sequencing and validated with qRT-PCR, ELISA and western blots. Results: Compared with HC, in IBD patients, IL-26 expression levels were elevated in the inflamed intestinal mucosa, and reduced in serum and PBMCs. IL-26 mRNA levels in PBMCs, but not serum IL-26 levels, were inversely correlated with disease activity in IBD. Furthermore, IL-26 mRNA levels in PBMCs were significantly lower in patients with complicated Crohn’s disease. A total of 1303 differentially expressed protein-coding genes were identified between untreated and IL-26-treated macrophages. The up-regulated genes showed enrichment in some inflammatory and immune-related processes and pathways. Additionally, GSEA showed that neutrophil, monocyte, and lymphocyte chemotaxis was significantly enriched in IL-26-treated macrophages. Further validation revealed that IL-26 promotes the secretion of multiple inflammatory cytokines and chemokines and upregulates the expression of adhesion molecules, MMP-8, and MMP-9 while inhibiting MMP-1 in macrophages. Conclusions: Compared with HC, in IBD patients, IL-26 levels were elevated in the inflamed intestinal mucosa, and reduced in the peripheral blood. The transcriptional changes in macrophages exposed to IL-26 suggest that IL-26 may amplify the aberrant immune response in IBD by activating macrophages.